Insulin-like growth factor-1 (IGF-1) selectively modulates the metabolic and lipid profile of bovine embryos according to their kinetics of development - Annes, Kelly; de Lima, Camila Bruna; Ispada, Jéssica; dos Santos, Érika Cristina; Fontes, Patrícia Kubo; Nichi, Marcílio; Nogueira, Marcelo Fabio Gouveia [UNESP]; Sudano, Mateus José; Milazzotto, Marcella Pecora (Elsevier, 2023)
Supplementation of culture media with IGF-1 during in vitro culture of embryos has had controversial results over the years. In the present study, we show that differences previously observed in response to IGF addition might be related to intrinsic heterogeneity of the embryos. In other words, the effects exerted by IGF-1 are dependent on the characteristics of the embryos and their ability to modulate metabolism and overcome stressful conditions, such as the ones found in a non-optimized in vitro culture system. To test this hypothesis, in vitro produced bovine embryos with distinct morphokinetics (fast- and slow-cleavage) were submitted to treatment with IGF-1 and then evaluated for embryo production rates, total cell number, gene expression and lipid profile. Our results show that remarkable differences were found when fast and slow embryos treated with IGF-1 were compared. Fast embryos respond by upregulating genes related to mitochondrial function, stress response, and lipid metabolism, whereas slow embryos presented lower mitochondrial efficiency and lipid accumulation. We conclude that indeed the treatment with IGF-1 selectively affects embryonic metabolism according to early morphokinetics phenotypes, and this information is relevant for decision-making in the design of more appropriate in vitro culture systems.
Keywords: Bovine; Embryos; IGF; Lipids; Morphokinetics